Peningkatan Pengetahuan dan Keterampilan Guru IPA Kabupaten Sukabumi dalam Pengembangan Media Pembelajaran - Indarini Dwi Pursitasari; Dadang Jaenudin; Leny Heliawati (Jurnal Pemberdayaan Masyarakat, 2024)
Learning media is created to enable interpersonal interaction between teachers and students and provide a significant learning situation for students. The problem that arises in MGMP Science Sukabumi Regency is that teachers still find it difficult to make learning videos, need learning applications that are easily accessible, need innovative and creative learning media, so this service activity is carried out with the aim of developing and implementing learning media systematically based on the needs and characteristics of students. This media is also aimed at changing behavior according to the goals to be achieved which is carried out by three methods, namely preparation, implementation, and evaluation. This activity resulted in an understanding of teacher competence in dealing with generation Z and an understanding of materials practices for making interesting and interactive learning media based on previously prepared teaching materials This solution was chosen because it was in accordance with the ability and experience of the implementer, which has produced interesting and interactive learning media for students so that it has a good impact on partners. An analysis of the condition of the Sukabumi Regency MGMP IPA shows that PKM partners have done many things to improve the competence of science teachers in their area.